The Benefits of Philosophy for the Development of the Islamic Educational Management Curriculum - Devi Yonesi; Made Saihu (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The development of the Islamic Education Management curriculum often faces a fundamental problem in the form of a weak philosophical foundation that causes the curriculum to be less directed and does not fully reflect Islamic values. This study aims to explain the benefits of philosophy for curriculum development by examining the role of onology, epistemology, and axiology in providing direction, basis, and value orientation for the educational process. The method used is a literature study through literature analysis that discusses the relationship between Islamic philosophy and curriculum design. The results of the study show that ontology helps establish human nature as the basis of educational goals, epistemology strengthens the selection of sources and the truth of knowledge included in the curriculum, while axiology ensures that the entire educational process is oriented towards the formation of character and moral values. These three aspects make a significant contribution to the preparation of objectives, material selection, learning methods, evaluation, and curriculum adaptation to the development of science and technology. This study concludes that philosophy has a strategic role in building a curriculum that is holistic, integrative, and in line with Islamic values so that it is able to produce graduates who are competent, characterful, and morally responsible.